Aspects of paediatric gastro oesophageal scintigraphy - Wynchank, Sinclair (Department of Paediatrics and Child Health, 2018)
This work is concerned with the application of scintigraphy in studies of foregut motility in paediatric patients; notably oesophageal transit during swallowing, gastro oesophageal reflux (GOR) and stomach emptying as measured by the gastric contents 30 and 120 minutes after deglutition of liquid. Relevant anatomy, physiology, pathophysiology and non-radioisotopic methods of gastro oesophageal examination are outlined. The extremely important question of dose deposited by ionising radiation in paediatric patients is also considered. Because currently available estimations of absorbed dose after swallowing non- absorbable radionuclides are unsatisfactory and often contradictory, a new model was derived. It is based on more physiological principles than previous models, with a continuously varying exponential passage between four compartments in the gastrointestinal tract. From a review of previous work and our experience, a standard method of examination was developed. There is emphasis on normal physiological manoeuvres. The broad extent of useful information available in the study stems from the positions in which the patient is investigated, the quantity of labelled fluid swallowed, its physiological nature and observations of oesophageal transit, GOR, gastric emptying and pulmonary aspiration after two hours. The wide range of paediatric problems amenable to investigation by this means is described, including those of a life-threatening nature. Also, the importance of using this examination to determine the likelihood of successful surgical intervention in the gastro oesophageal region is explained. By using the observations made during swallows in neonates, the closure of the lower oesophageal sphincter (LOS) was observed during a short series of rapid deglutitions. This extends previous knowledge of the function of the neonatal LOS. These findings were very clearly demonstrated by the condensed image technique. A comparison between the abilities of radiology and scintigraphy to detect GOR in paediatric patients, with and without oesophagitis, gives unequivocal results in favour of scintigraphy. Two independent clear correlations between oesophageal transit time and the severity of GOR and age are demonstrated by variance and correlation analysis. The mean duration of GOR, maximum height of a GOR, gastric contents 30 and 120 min after deglutition, the effect of the nature of liquid swallowed and age are also examined and their relations are described. The application of the method to assess drug response is illustrated by the paediatric use of cisapride, an experimental drug which increases acetylcholinesterase release. The deductions from this work include values of the radiation dose deposited in paediatric patients of various ages, after swallowing non- absorbed Tc-99m compounds. Other contributions are a scintigraphic means to allow recognition of the importance of oesophageal dysmotility in paediatrics, especially in the absence of GOR and its relevance to the efficacy of surgery in cases of apparent GOR. Also, this gastro oesophageal scintigraphic study provided information on the paediatric use of cisapride, the relevance of GOR to repeated respiratory problems and the recognition of a new paediatric syndrome analogous to the diffuse oesophageal spasm syndrome of adulthood. It has been demonstrated that a routine, uncomplicated, paediatric scintigraphic examination, useful for investigating a wide range of problems in both a first and third world setting is possible for a nuclear medicine practitioner with normally available radiopharmaceuticals, equipment and radiographical expertise.